Making the message clear: Visualizing mRNA localization - Weil, T; Parton, R; Davis, I (2010)
Localized mRNA provides spatial and temporal protein expression essential to cell development and physiology. To explore the mechanisms involved, considerable effort has been spent in establishing new and improved methods for visualizing mRNA. Here, we discuss how these techniques have extended our understanding of intracellular mRNA localization in a variety of organisms. In addition to increased ease and specificity of detection in fixed tissue, in situ hybridization methods now enable examination of mRNA distribution at the ultrastructural level with electron microscopy. Most significantly, methods for following the movement of mRNA in living cells are now in widespread use. These include the introduction of labeled transcripts by microinjection, hybridization based methods using labeled antisense probes and complementary transgenic methods for tagging endogenous mRNAs using bacteriophage components. These technical innovations are now being coupled with super-resolution light microscopy methods and promise to revolutionize our understanding of the dynamics and complexity of the molecular mechanism of mRNA localization. © 2010 Elsevier Ltd.